A method for preparing biodegradable aerogel composite functional filaments

TiO2 nanoparticles were adsorbed on the surface of graphene microspheres through electrostatic self-assembly technology and mixed with chitosan solution to prepare TiO2/graphene porous aerogel, which solved the non-degradation of petroleum-based polymer materials and the catalytic activity of TiO2 powder. The problem of reducing the visible light degradation of polymers and environmentally friendly material applications.

CN116005283BActive Publication Date: 2025-02-07SHANDONG RARE TECH DEV CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211705161.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2025-02-07
Estimated Expiration
2042-12-29

AI Technical Summary

Technical Problem

In the prior art, petroleum-based polymer materials are non-degradable, resulting in environmental pollution, and the agglomeration of TiO2 powder in the polymer leads to a decrease in catalytic activity.

Method used

TiO2 nanoparticles were adsorbed on the surface of graphene microspheres through electrostatic self-assembly technology and mixed with chitosan solution. TiO2/graphene porous aerogel was prepared by freeze-drying by sol-gel method to prevent nanoparticles from being in the polymer Reunion.

Benefits of technology

The visible light degradation of polymers is achieved, the photocatalytic activity of TiO2 is improved, and the material is non-toxic, harmless and degradable to the human body, and will not cause secondary pollution to the environment, reducing costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for preparing a degradable aerogel composite functional filament, comprising the following steps: dispersing graphene microspheres in a cationic solution so that the surface of the graphene microspheres is positively charged, dispersing TiO2 in an anionic solution so that the surface of the graphene microspheres is negatively charged, mixing the two, and adsorbing the negatively charged TiO2 on the surface of the positively charged graphene microspheres to obtain a TiO2 / graphene microsphere suspension; dissolving chitosan in a glacial acetic acid solution and mixing with the TiO2 / graphene microsphere suspension obtained in step one; preparing aerogel by a sol-gel method and a low-temperature freeze-drying technology to obtain a photocatalytically degradable aerogel; crushing the photocatalytically degradable aerogel prepared in step two, and then blending with a polymer raw material, extruding granulation, and melt spinning. The composite functional filament prepared by the invention is characterized in that the original performance of the composite filament is maintained and the composite filament is degradable after a certain period of time under visible light without causing secondary pollution to the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of multifunctional fibers, and in particular to a method for preparing degradable aerogel composite functional filaments. Background Art

[0002] With the development of science and technology and the improvement of people's living standards, the use and demand of oil-derived polymer materials have continued to increase, which has led to the massive consumption of oil resources and white pollution problems, causing tremendous pressure on the environment. In order to solve the problem of non-degradable traditional plastics, new biodegradable plastics have gradually begun to enter people's lives. Vigorously developing and promoting biodegradable plastics is an important way to solve the above problems.

[0003] Photodegradable additives have attractive application prospects due to their excellent degradability and simple preparation process. Some particles, including TiO 2 , ZnO, and graphene have long been added to polymers to impart effective photodegradation capabilities. 2 As a non-toxic and excellent photocatalyst, it is often used to degrade various pollutants. It is also added to polymers. However, TiO 2 The powders tend to agglomerate in the polymer and react only under UV light.

[0004] In order to solve the TiO 2 The powder agglomerates in the polymer, resulting in a decrease in its catalytic activity. The present invention proposes to use electrostatic self-assembly technology to 2 The nanoparticles were adsorbed on the surface of graphene microspheres and mixed with chitosan solution to prepare TiO by freeze drying using the sol-gel method. 2 / Graphene porous aerogel. Graphene microspheres refer to graphene nanosheets that have been physically or chemically formed into wrinkled or cavitated microsphere structures. They have a large specific surface area and excellent light absorption, which can promote the 2 The photocatalytic activity of aerogels can be improved, thereby improving the photocatalytic efficiency. In addition, aerogels have an extremely low apparent density (0.003-0.3 g / cm 3 ), large specific surface area (100~2400m 2 / g), high porosity (80-99.8%) and low thermal conductivity [10-40mW / (m·K)]. In particular, aerogel materials based on biomass materials have excellent biocompatibility. Aerogel composite functional filaments prepared by blending multifunctional aerogels with polymer raw materials have the advantages of light weight, degradability and good wearability.

[0005] In the prior art, degradable aerogel composite materials generally use degradable polymer materials or add degradable fillers. For example, patent CN102516566A introduces a method for preparing biodegradable polymer nanoparticles. An oil phase solution containing a biodegradable polymer is mixed with an aqueous phase solution containing a surfactant; the film is passed through a manual film passing device at a uniform speed for several times to obtain a biodegradable polymer emulsion of uniform size. Patent CN202210827584.4 discloses a degradable polyester fabric and a preparation method thereof. The degradable polyester fabric is a degradable composition obtained by mixing polylactic acid and polyterephthalic acid, butylene adipate, straw fiber, glutinous rice flour, degradable additives and polycaprolactone; other raw materials are added to mix, extruded and granulated, and then melt-spun. The existing functional fibers have achieved a certain degradable effect, but have not fundamentally solved the problem of non-degradability of petroleum-based polymer materials and their pollution to the environment. Summary of the invention

[0006] In order to overcome the defects in the prior art, the present invention provides a method for preparing a degradable aerogel composite functional filament, wherein TiO 2 / graphene microsphere composite photocatalyst, using the excellent light absorption performance of graphene to improve the TiO 2 Photocatalytic activity was used to achieve visible light degradation of polymers. Chitosan solution was used as a dispersant to dissolve TiO 2 / graphene was dispersed in chitosan solution and multifunctional composite aerogel was prepared by sol-gel method to avoid agglomeration of nanoparticles in polymer; compared with other preparation methods of degradable polymer materials, TiO 2 / Graphene / chitosan components are non-toxic, harmless and degradable to the human body and will not cause secondary pollution to the environment, which greatly reduces the cost and can be used in large-scale applications.

[0007] Technical Solution

[0008] A method for preparing a degradable aerogel composite functional filament comprises the following steps:

[0009] Step 1: Graphene microspheres and TiO 2 Electrostatic self-assembly: Graphene microspheres are dispersed in a cationic solution to make their surface positively charged, and TiO 2 Dispersed in anionic solution to make its surface negatively charged, the two are mixed, and the negatively charged TiO 2 TiO 2 / graphene suspension.

[0010] Step 2: Preparation of photocatalytically degradable aerogel: Dissolve chitosan in glacial acetic acid solution and mix with the TiO 2 / graphene suspension is mixed, and aerogel is prepared through a sol-gel method and low-temperature freeze-drying technology. The aerogel is then crushed to obtain porous nanomaterials to obtain photocatalytic degradable aerogel.

[0011] Step 3: Preparation of multifunctional composite filaments: The photocatalytically degradable aerogel prepared in step (2) is crushed and then blended with a polymer raw material, extruded into granules, and melt-spun.

[0012] Further, in step 1, the graphene microspheres were dispersed in hexadecyltrimethylammonium bromide, the graphene microsphere concentration was 5 mg / mL, and the dispersion was carried out at high speed (5000 rpm) for 10 min at room temperature. 2 Dispersed in calcium dodecylbenzene sulfonate, TiO 2 The concentration was 30 mg / mL, and the dispersion was carried out at high speed (5000 rpm) for 10 min at room temperature. Then the graphene dispersion and TiO 2 The dispersions were uniformly mixed in a volume ratio of 1:1 and stirred at 500 rpm for 10 min.

[0013] Further, in step 2, chitosan (1-5 wt%) was added to a glacial acetic acid solution (2% V / V), stirred at room temperature for 3-5 h at a speed of 300 rpm, and then the TiO prepared in step 1 was added to the mixture. 2 / The graphene dispersion and chitosan solution were evenly mixed in a volume ratio of 1:5 and cast into a film with a thickness of 0.1-1 cm. Finally, the prepared gel was precooled (-20°C, frozen for 2 h) and then freeze-dried to prepare aerogel.

[0014] Furthermore, in step 3, the photocatalytically degradable aerogel is crushed: the particle size after crushing is 100nm-3μm, and the photocatalytically degradable aerogel is crushed and blended with polyester raw materials, extruded granulated, and melt-spun: the photocatalytically degradable aerogel is crushed (1-10wt%) and blended with polymer raw materials (90-95wt%) for extrusion granulation and melt spinning, and the melting temperature is 200-300°C.

[0015] Furthermore, during the processing of step 3, the fiber yield rate is improved by adding additives such as defoaming agents.

[0016] Furthermore, the polymer raw materials include but are not limited to polyurethane, nylon 6, and acrylic.

[0017] Furthermore, the cationic solution includes but is not limited to hexadecyltrimethylammonium bromide, octadecenylamine acetate, and aminopropylamine dioleate; the anionic solution includes but is not limited to sodium hexametaphosphate, calcium lignin sulfonate, calcium dodecylbenzene sulfonate and the like.

[0018] Furthermore, the aerogel composite functional filament is composed of the following components in parts by weight: 70-90 wt% of polymer raw material, 5-10 wt% of chitosan, 2 1-5wt%, graphene microspheres 0.1-1wt%, other additives 1-3wt%.

[0019] Beneficial Effects

[0020] Compared with the prior art, the beneficial effects of the present invention are:

[0021] 1. TiO 2 Preparation of TiO by electrostatic self-assembly with graphene microspheres 2 / graphene microsphere composite photocatalyst, using the excellent light absorption performance of graphene to improve the TiO 2 Photocatalytic activity, achieving visible light degradation of polymers;

[0022] 2. Use chitosan solution as dispersant to dissolve TiO 2 / graphene microsphere suspension was mixed with chitosan solution and multifunctional composite aerogel was prepared by sol-gel method to avoid agglomeration of nanoparticles in polymer;

[0023] 3. Compared with other preparation methods of degradable polymer materials, TiO 2 / Graphene / chitosan components are non-toxic, harmless and degradable to the human body and will not cause secondary pollution to the environment, which greatly reduces the cost and can be used in large-scale applications. DETAILED DESCRIPTION

[0024] In order to better illustrate the content of the present invention, the following is a description in conjunction with an implementation example:

[0025] The invention discloses a method for preparing a degradable aerogel composite functional filament, comprising the following steps:

[0026] Step 1: Graphene microspheres and TiO 2 Electrostatic self-assembly: Graphene microspheres are dispersed in a cationic solution to make their surface positively charged, and TiO 2 Dispersed in anionic solution to make its surface negatively charged, the two are mixed, and the negatively charged TiO 2 TiO 2 / graphene microsphere suspension.

[0027] Step 2: Preparation of photocatalytically degradable aerogel: Dissolve chitosan in glacial acetic acid solution and mix with the TiO 2 / graphene microsphere suspension is mixed, and aerogel is prepared through a sol-gel method and low-temperature freeze-drying technology. The aerogel is then crushed to obtain porous nanomaterials to obtain photocatalytic degradable aerogel.

[0028] Step 3: Preparation of multifunctional composite filaments: The photocatalytically degradable aerogel prepared in step (2) is crushed and then blended with a polymer raw material, extruded into granules, and melt-spun.

[0029] Further, in step 1, the graphene microspheres were dispersed in hexadecyltrimethylammonium bromide, the graphene microsphere concentration was 5 mg / mL, and the dispersion was carried out at high speed (5000 rpm) for 10 min at room temperature. 2 Dispersed in calcium dodecylbenzene sulfonate, TiO 2 The concentration was 30 mg / mL, and the dispersion was carried out at high speed (5000 rpm) for 10 min at room temperature. Then the graphene dispersion and TiO 2 The dispersions were uniformly mixed in a volume ratio of 1:1 and stirred at 500 rpm for 10 min.

[0030] Further, in step 2, chitosan (1-5 wt%) was added to a glacial acetic acid solution (2% V / V), stirred at room temperature for 3-5 h at a speed of 300 rpm, and then the TiO prepared in step 1 was added to the mixture. 2 / The graphene microsphere suspension and chitosan solution were mixed evenly in a volume ratio of 1:5 and cast into a film with a thickness of 0.1-1 cm. Finally, the prepared gel was precooled (-20°C, frozen for 2 h) and then freeze-dried to prepare aerogel.

[0031] Furthermore, in step 3, the photocatalytically degradable aerogel is crushed: the particle size after crushing is 100nm-3μm, and the photocatalytically degradable aerogel is crushed and blended with polyester raw materials, extruded granulated, and melt-spun: the photocatalytically degradable aerogel is crushed (1-10wt%) and blended with polymer raw materials (90-95wt%) for extrusion granulation and melt spinning, and the melting temperature is 200-300°C.

[0032] Furthermore, during the processing of step 3, the fiber yield rate is improved by adding additives such as defoaming agents.

[0033] Furthermore, the polymer raw materials include but are not limited to polyurethane, nylon 6, and acrylic.

[0034] Furthermore, the cationic solution includes but is not limited to hexadecyltrimethylammonium bromide, octadecenylamine acetate, and aminopropylamine dioleate; the anionic solution includes but is not limited to sodium hexametaphosphate, calcium lignin sulfonate, calcium dodecylbenzene sulfonate and the like.

[0035] Furthermore, the aerogel composite functional filament is composed of the following components in parts by weight: 70-90 wt% of polymer raw material, 5-10 wt% of chitosan, 2 1-5wt%, graphene microspheres 0.1-1wt%, other additives 1-3wt%.

[0036] Specifically, (1) graphene microspheres and TiO 2 Electrostatic self-assembly of:

[0037] The graphene microspheres were dispersed in cationic hexadecyltrimethylammonium bromide at a concentration of 5 mg / mL and dispersed at high speed (5000 rpm) for 10 min at room temperature to make their surface positively charged. 2 The graphene dispersion was dispersed in anionic calcium dodecylbenzene sulfonate at a concentration of 30 mg / mL and dispersed at high speed (5000 rpm) for 10 min at room temperature to make its surface negatively charged. 2 The dispersions were uniformly mixed at a volume ratio of 1:1 and stirred at 500 rpm for 10 min. 2 TiO can be obtained by adsorbing on the positively charged graphene surface. 2 / graphene microsphere dispersion;

[0038] (2) Preparation of photocatalytic degradable aerogel:

[0039] Dissolve chitosan (1-5 wt%) in glacial acetic acid solution (2% V / V) and stir at room temperature for 3-5 h at a speed of 300 rpm. Then, mix the dispersion prepared in step 1 and the chitosan solution in a volume ratio of 1:5 and cast into a film with a thickness of 0.1-1 cm. Finally, precool the prepared gel (-20°C, frozen for 2 h) and then prepare an aerogel by freeze drying.

[0040] (3) Preparation of multifunctional composite filaments:

[0041] The photocatalytically degradable aerogel prepared in step 2 is crushed and then blended with a polymer raw material, extruded into granules, and melt-spun.

[0042] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0043] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the technical solutions of the present invention have been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a degradable aerogel composite functional filament, characterized in that: The steps include: Step 1: Electrostatic self-assembly of graphene microspheres and TiO2: Disperse graphene microspheres in a cationic solution to make their surface positively charged, disperse TiO2 in an anionic solution to make their surface negatively charged, mix the two, and adsorb the negatively charged TiO2 on the surface of the positively charged graphene microspheres to obtain a TiO2 / graphene suspension; Step 2: Preparation of photocatalytically degradable aerogel: dissolving chitosan in a glacial acetic acid solution and mixing it with the TiO2 / graphene suspension obtained in step 1, preparing aerogel by a sol-gel method and low-temperature freeze-drying technology, and then crushing the aerogel to obtain a porous nanomaterial to obtain a photocatalytically degradable aerogel; Step 3: Preparation of multifunctional composite filaments: crushing the photocatalytic degradable aerogel prepared in step 2, blending with polymer raw materials, extruding granulation, and melt spinning; The cationic solution includes hexadecyltrimethylammonium bromide, octadecenylamine acetate, and aminopropylamine dioleate; the anionic solution includes sodium hexametaphosphate, calcium lignin sulfonate, and calcium dodecylbenzene sulfonate.

2. The method for preparing a degradable aerogel composite functional filament according to claim 1, characterized in that: In step 1, graphene microspheres are dispersed in hexadecyltrimethylammonium bromide, the graphene microsphere concentration is 5 mg / mL, and the speed of high-speed dispersion is 5000 rpm at room temperature for 10 min. TiO2 is dispersed in calcium dodecylbenzenesulfonate, the TiO2 concentration is 30 mg / mL, and the speed of high-speed dispersion is 5000 rpm at room temperature for 10 min. Subsequently, the graphene dispersion and the TiO2 dispersion are uniformly mixed in a volume ratio of 1:1 and stirred at 500 rpm for 10 min.

3. The method for preparing a degradable aerogel composite functional filament according to claim 2, characterized in that: In step 2, chitosan is added to a glacial acetic acid solution, the mass fraction of chitosan is 1-5 wt%, and the volume fraction of the glacial acetic acid solution is 2% V / V. The mixture is stirred at room temperature for 3-5 h at a speed of 300 rpm. Subsequently, the TiO2 / graphene microsphere suspension prepared in step 1 is evenly mixed with the chitosan solution in a volume ratio of 1:5 and cast into a film with a thickness of 0.1-1 cm. Finally, the prepared gel is precooled at -20 °C for 2 h, and then the aerogel is prepared by freeze drying.

4. The method for preparing a degradable aerogel composite functional filament according to claim 3, characterized in that: In step three, the photocatalytically degradable aerogel is crushed: the particle size after crushing is 100 nm-3 μm, and the photocatalytically degradable aerogel is crushed and blended with a polyester raw material, extruded into granules, and melt-spun: the photocatalytically degradable aerogel is crushed and blended with a polymer raw material, extruded into granules, and melt-spun, the melting temperature is 200-300°C, the mass fraction of the photocatalytically degradable aerogel is 1-10 wt%, and the mass fraction of the polymer raw material is 90-95 wt%.

5. The method for preparing a degradable aerogel composite functional filament according to claim 4, characterized in that: The polymer raw materials include polyurethane, nylon 6 and acrylic fiber.

6. The method for preparing a degradable aerogel composite functional filament according to claim 1, characterized in that: During the processing of step three, the fiber yield rate is improved by adding a defoaming agent.

7. The method for preparing a degradable aerogel composite functional filament according to claim 6, characterized in that: The aerogel composite functional filament is composed of the following components in parts by weight: 70-90 wt % of polymer raw material, 5-10 wt % of chitosan, 1-5 wt % of TiO2, 0.1-2 wt % of graphene microspheres, and 1-3 wt % of other additives.

Citation Information

Patent Citations

  • Method for preparing biodegradable polymer nano particles

    CN102516566A

  • Degradable polyester fabric and preparation method thereof

    CN115012067A

  • Preparation method of aerogel modified synthetic fiber and synthetic fiber prepared by same

    CN103388193A

  • Preparation method of graphene / chitosan adsorbent resin

    CN103464122A

  • Method for synthesizing titanium dioxide / graphene nano composite material

    CN105903462A